Degrees of confidence and modal words in Lithuanian - Usonienė, Aurelija (Lietuvių kalba, 2007)
Probability, an epistemic qualification of modality in language, is considered to be a gradable category. The paper will look at the qualitative and quantitative parameters of equivalence between the realizations of high and low degree of probability in English and Lithuanian. The focus of the contrast is on modal words and particles in Lithuanian and their correspondences in English. The purpose of this parallel corpus-based pilot study is to see whether there is any language-specific conceptualization of probability in Lithuanian.